2004
DOI: 10.7164/antibiotics.57.739
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Copalyl Diphosphate Synthase Gene in an Actinomycete Possessing the Mevalonate Pathway

Abstract: We have previously shown that gene clusters for biosyntheses of terpentecin and BE-40644, a diterpene antibiotic and a sesquiterpene antibiotic, respectively, were located in the adjacent mevalonate pathway gene clusters. In this study, a mevalonate pathway gene cluster was cloned from Streptomyces sp. strain KO-3988, which was known to produce furaquinocin A, employing a hybridization experiment using a 3-hydroxy-3-methyl glutaryl CoA (HMGCoA) reductase gene, which had been previously cloned from the strain K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 27 publications
0
52
0
Order By: Relevance
“…10, although the absolute stereochemistry of the product remains unclear. However, this is the first example of an enzyme of prokaryotic origin with this function [79].…”
Section: Analyses Of the Flanking Regions Of Mevalonate Pathway Gene mentioning
confidence: 87%
See 1 more Smart Citation
“…10, although the absolute stereochemistry of the product remains unclear. However, this is the first example of an enzyme of prokaryotic origin with this function [79].…”
Section: Analyses Of the Flanking Regions Of Mevalonate Pathway Gene mentioning
confidence: 87%
“…First, we analyzed the flanking regions of one of the MV clusters (MV1) and found 4 ORFs that could encode a putative cytochrome P450 (ORF1), a diterpene cyclase (ORF2), an unknown protein (ORF3), and a GGDP (C 20 ) synthase gene (ORF4) in the upstream region of the MV1 cluster [79] (Fig. 5C), although we did not find genes related to the biosynthesis of furaquinocin A.…”
Section: Analyses Of the Flanking Regions Of Mevalonate Pathway Gene mentioning
confidence: 99%
“…In particular, the ent-CPP synthase from Streptomyces sp. strain KO-3988 (SkoCPS) [30], the terpentediene diphosphate synthase from Streptomyces griseolosporeus (SgTPS) [31], and the halimadienyl diphosphate synthase from Mycobacterium tuberculosis (MtHPS) [32], which are 499-511 aa in length. Further, in the initial characterization of the associated operon it was suggested that the corresponding gene encoded a 516 aa length protein [27], and this was the construct analyzed here.…”
Section: Resultsmentioning
confidence: 99%
“…We found recently that biosynthetic genes of terpentecin [12] and 3-hydroxypimeradiene (viguiepinol) [14,15], both of which are diterpene compounds produced by actinomycetes, were located in flanking regions of the genes encoding geranylgeranyl diphosphate synthase (GGPPS), which supplies a direct precursor of diterpene compounds. Hence, we first tried to clone a GGPPS gene in order to use it as a probe to clone an entire BCA biosynthetic gene cluster.…”
Section: Cloning Of a Ggpps Gene By Pcrmentioning
confidence: 99%
“…Cloning of Polyprenyl Diphosphate Synthase Genes by PCR Three sets of primers were designed, based on the conserved amino acid sequences of polyprenyl diphosphate synthase genes, which had been cloned from terpentecin [22], furaquinocin A [14,15], and BE-40644 [23] producers:…”
Section: Dna Isolation and Manipulationmentioning
confidence: 99%